Генеративне розмноження Adenium obesum (Forssk.) Roem. et Schult. в умовах інтродукції - Aviekin, Ya.V.; Gaidarzhy, M.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
There have been studied the phenology and morphological features of the generative organs of Adenium obesum (Forssk.) Roem. et Schult. under the introduction conditions to identify the factors which hamper the artificial cross-pollination and production of viable seeds. It has been found that the budding of plants lasts nearly 90 days, flowering – 30–35 days, fruit ripening – 110–120 days. The flowering of one flower lasts for 5 days, but the pollination is possible only in the first two days, because the link between a flower style and carpers is broken further. Moreover, the high pollen fertility is observed within 3–4 days of blooming. At artificial pollination, mature fruits produce (80 ± 30) seeds. The germination of freshly harvested seeds is 96 %. The procedures at artificial pollination of flowers of A. obesum have been proposed.